A Differential Cooperative Positioning Approach for Multi-Device Positioning Improvement - Trigos Guevara, William Javier; Pedraza Ferreira, Gabriel; Ramos Pollan, Raúl (Ingeniería Solidaria, 2019)
Introduction: This publication is the product of research developed within the research lines of the Advanced and Large-scale Computing (Cage) research group throughout 2018, which supports the work of a master’s degree in Systems Engineering at the Industrial University of Santander.Objetive: An approach to a cooperative positioning algorithm is described in this paper, where a set of devices exchange GPS satellite observables and distance estimations with nearby devices in order to increase their positioning accuracy.Methodology: Different scenarios are established where GPS receivers exchange satellite information, using different ionospheric correction models, with the purpose of evaluating which conditions potentially improve the position accuracy.Conclusions: The results show our approach yields increased accuracy when all receivers use the same ionospheric correction model. Moreover, it was observed that the noise levels and uncertainty usually due to factors related to distance from remote devices to the main receiver did not influence positioning improvement when the separation between receiver pairs was large.Originality: The proposed algorithm allows for exploitation of the nature of the problem without increasing complexity at the hardware and software level, and to offer a low-cost cooperative positioning solution alternative.Restrictions: The results presented in the document are based on the execution of the cooperative algorithm using Rinex files of gnss reference stations. So, for scenarios in which the separation distances between reference stations are very high, the error levels in cooperative positioning can be very large.
Keywords: Cooperative Positioning; Differential Positioning; Weighted Least Squares; Single Frequency GPS Receivers; Matrix Of Direction Cosines